Tolerance analysis of flicker Pst short term perceptibility assessment for one minute observation time - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
This paper present the tolerance analysis and evaluation of flicker severity Pst short term perceptibility assessment for 1 minute observation time based on IEC61000-4-15 flickermeter standard. The evaluation approach takes a complete range of standard rectangular modulated test waveform set for evaluation of both 10 minutes and the 1 minute observation time. The tolerance is then derived from the error evaluated from Pst of 1 and 10 minutes observation time. The proposed 20% tolerance is then verified with actual recorded waveform from the field. The result shows that the proposed tolerance is generally valid for 1 minute Pst assessment with one conditional limitation. The proposed tolerance serves as a supplementary guide for 1 minute Pst assessment to compliment the 10 minutes Pst assessment. 2012 IEEE.